Effect of Truncating AUC at 12, 24 and 48 hr When Evaluating the Bioequivalence of Drugs with a Long Half‐Life. Issue 1 (14th July 2015) - Moreno, Isabel; Ochoa, Dolores; Román, Manuel; Cabaleiro, Teresa; Abad‐Santos, Francisco
Abstract: Bioequivalence studies of drugs with a long half‐life require long periods of time for pharmacokinetic sampling. The latest update of the European guideline allows the area under the curve (AUC) truncated at 72 hr to be used as an alternative to AUC0– t as the primary parameter. The objective of this study was to evaluate the effect of truncating the AUC at 48, 24 and 12 hr on the acceptance of the bioequivalence criterion as compared with truncation at 72 hr in bioequivalence trials. The effect of truncated AUC on the within‐individual coefficient of variation (CVw ) and on the ratio of the formulations was also analysed. Twenty‐eight drugs were selected from bioequivalence trials. Pharmacokinetic data were analysed using WinNonLin 2.0 based on the trapezoidal method. Analysis of variance (anova ) was performed to obtain the ratios and 90% confidence intervals for AUC at different time‐points. The degree of agreement of AUC0–72 in relation to AUC0–48 and AUC0–24, according to the Landis and Koch classification, was 'almost perfect'. Statistically significant differences were observed when the CVw of AUC truncated at 72, 48 and 24 hr was compared with the CVw of AUC0–12 . There were no statistically significant differences in the AUC ratio at any time‐point. Compared to AUC0–72, Pearson's correlation coefficient for mean AUC, AUC ratio and AUC CVw was worse for AUC0–12 than AUC0–24 or AUC0–48 . These preliminary results could suggest that AUC truncation at 24 or 48 hr is adequate to determine whether two formulations are bioequivalent.